Production Process for Memory Foam Mattresses in Peru - Strobbe, Caterina (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4821 This article aims to define the technological viability of the installation of a memory foam mattress plant to provide users a better quality of life. The most relevant topics of the study are product definition and production process. These tools are important to understand the process and establish the critical points for mattress production.